Vitrectomy for breakthrough bleeding in age related macular degeneration and polypoidal choroidal vasculopathy in a Malaysian hospital - Bastion, MLC; Amelah, MAQ; Wong, HS (Department of Surgery, UKM Medical Centre, 2012)
This study aimed to review the risk factors and clinical outcomes of patients undergoing pars planar vitrectomy (PPV) for breakthrough bleeding (BTB) from age related macular degeneration (AMD) and polypoidal choroidal vasculopathy (PCV). We performed a retrospective review of medical records of 346 patients operated by the vitreoretinal unit at Universiti Kebangsaan Malaysia Medical Centre (UKMMC), Kuala Lumpur, Malaysia from January 2008 - June 2011. We found eight eyes of 8 patients with AMD/IPCV-related BTB who underwent PPV. Mean age of patients was 64.4 years (range 41-80 years) with 5 males. Five were Chinese. Duration of symptoms ranged from days to months. Four patients were on anti-coagulants. Two had history of prior photodynamic therapy. There were five cases of PCV, of which three were macular in location. All three cases of AMD were macular. Intraoperative intravitreal ranibizumab injection was given in three cases and two had combined vitrectomy and cataract extraction. All cases reported improvement in visual acuity with four cases achieving 6/60 or better post operatively including two cases of extramacular PCV achieving 6/9 vision. Mean follow-up was 60 weeks. Postoperative complications included retinal tear and detachment in one case, reattached on reoperation. Six patients had a history of hypertension including one individual with stroke. Our small series indicates a predominance of Chinese individuals with BTB. Usage of anticoagulants and hypertension may be a predisposing factor. Better visual prognosis occurs with extramacular lesions which tend to be of PCV type.